1999
DOI: 10.2134/jeq1999.00472425002800060008x
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Cadmium‐109 and Zinc‐65 in Soil Influenced by Equilibration Time, Temperature, and Organic Matter

Abstract: Partitioning of 109Cd and 65Zn fractions in an alum shale soil as affected by time, temperature, and organic matter was investigated. The soil was extracted sequentially by H20 (F1), 1 M NH4OAc at pH 7 (F2), 1 M NH4OAc at pH 5 (F3), 0.04 M NH2OH HCl (F4), 30% H2O2 (F5), and finally by 7 M HNO3 (F6). Sequential extraction of metals was performed on soil samples collected at time intervals ranging from 0.5 to 8760 h (1 yr) after spiking the soil with 109Cd and 65Zn. The soil was placed incipiently in temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 0 publications
3
46
1
4
Order By: Relevance
“…The result is contradictory to the finding that Cd was increased significantly in the mobile fractions in the soil with the addition of organic matter (Almas et al, 1999). The total soluble concentration of metal ions in soil solutions depends on the free metal ion concentration, the presence of inorganic and organic ligands and pH.…”
Section: Speciation In Whole Soilcontrasting
confidence: 70%
See 2 more Smart Citations
“…The result is contradictory to the finding that Cd was increased significantly in the mobile fractions in the soil with the addition of organic matter (Almas et al, 1999). The total soluble concentration of metal ions in soil solutions depends on the free metal ion concentration, the presence of inorganic and organic ligands and pH.…”
Section: Speciation In Whole Soilcontrasting
confidence: 70%
“…CaCl 2 -extractable Cu in some artificial soils, soluble and exchangeable Cu fractions in sandy soil and sandy loam were found to decrease over time (Han et al, 2001;Tom-Petersen et al, 2004; Daoust et al, 2006). In sequential chemical extraction experiment, Cd concentration decreased in the three mobile fractions with time (Almas et al, 1999). In this study, the effect of incubation time on free Cu 2+ and Cd 2+ concentrations showed different patterns for the four soils.…”
Section: Effects Of Incubation Time On Free and Soluble Metal Ion Conmentioning
confidence: 53%
See 1 more Smart Citation
“…The processes of diffusion were slow aging processes. Almås et al [50] also found that the transfer of Cd from solution to stable forms were significantly slower processes. The slow processes were due to inner-sphere surface complexation via partial or complete dehydration of surface species [12].…”
Section: Semi-mechanistic Models For Edta-cdmentioning
confidence: 95%
“…Segundo Muraoka (1991) 2 O elétron da camada K é puxado para dentro do núcleo e se transforma em nêutron (p + + e -k → n 0 ), e a vacância livre é ocupada por um elétron de outra camada, emitindo raio-X. Nas plantas, a atividade do radionuclídeo é representada pela atividade específica, dada por (DI; CONDRON; FROSSARD, 1997): O mais rigoroso método para avaliar a biodisponibilidade de íons metálicos no solo é pela medida direta da porção lábil, usando a técnica de diluição isotópica com traçadores radioativos (MURAOKA; NEPTUNE; NASCIMENTO FILHO, 1983a;1983b;NAKHONE;YOUNG, 1993;HAMON et al, 1998;SALBU, 1999;SMOLDERS et al, 1999;STANHOPE et al, 2000;SINGH, 2001 Figura 2 -Esquema de decaimento do 109 Cd ( 109m Ag). O número entre parênteses indica o valor da energia em keV.…”
Section: Técnica Isotópicaunclassified